Human rights and Europe - "Beddard, Ralph" (London, 1980)
The book considers the impact that the European Convention on Human Rights has had on the lives of those within the twenty-six Member States of the Council of Europe by selectively analyzing those parts of its large and complex case law that give an insight into the development of European human rights.
Keywords: European-Convention on human rights